STUDI KEPUASAN KONSUMEN MENGGUNAKAN EMPAT DIMENSI SERVQUAL PADA AREA PUBLIK TERMINAL 3 BANDARA CHANGI SINGAPURA - Andini Risfandini (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2019)
SERVQUAL is one of the model that is frequently used to measure customer satisfaction regarding the service quality. This study is using 4 dimensions of SERVQUAL to measure customer satisfaction about service quality in Changi Airport public area terminal 3 Singapore. The main objective of this study is to analyze the satisfaction level of Changi Airport’s customers of service quality in the public area in Terminal 3. In order to achieve this main objective, the following sub objectives were set namely: (1)to investigate whether there is a gap between customer expectations and customer perception of service quality in Changi Airport public area terminal 3; (2)to identify the significant factors that affecting customer expectations of service quality in Changi Airport public area terminal 3; (3)To identify the significant factors that affecting customer perception of service quality in Changi Airport Public Area terminal 3. Data was collected using survey questionnaire with Likert scale, it was analyzed using SPSS 21 using descriptive statistics, two tailed test, and faktor analysis. .The factors that have significant impact on customers’ expectations are assurance and security, comfort and convenience, safety and service, ambience and accessibility. While the customers’ perception of service quality is influenced by convenience and service, comfort, ambience and cleanliness, safety, accessibility and security factors.